The periaxonal space of crayfish giant axons (The Rockefeller University Press, 1983)
The influence of the glial cell layer on effective external ion concentrations has been studied in crayfish giant axons. Excess K ions accumulate in the periaxonal space during outward K+ current flow, but at a rate far below that expected from the total ionic flux and the measured thickness of the space. At the conclusion of outward current flow, the external K+ concentration returns to normal in an exponential fashion, with a time constant of approximately 2 ms. This process is about 25 times faster than is the case in squid axons. K+ repolarization (tail) currents are generally biphasic at potentials below about -40 mV and pass through a maximum before approaching a final asymptotic level. The initial rapid phase may in part reflect depletion of excess K+. After block of inactivation and reversal of the Na+ concentration gradient, we could demonstrate accumulation and washout of excess Na ions in the periaxonal space. Characteristics of these processes appeared similar to those of K+. Crayfish glial cell ultrastructure has been examined both in thin sections and after freeze fracture. Layers of connective tissue and extracellular fluid alternate with thin layers of glial cytoplasm. A membranous tubular lattice, spanning the innermost glial layers, may provide a pathway allowing rapid diffusion of excess ions from the axon surface.